The Effectiveness of World Bank Support for Community-Based and -Driven Development : Safeguard Policy Review - Whitford, Peter; Mathur, Kavita (World Bank, Washington, DC, 2021)
The Safeguards Policy Review is one of two thematic studies, called the effectiveness of World Bank support for community-based and -driven development, (CBD/CDD Study). The study reviewed project appraisal, supervision, and completion documents for a sample of 84 projects to assess their compliance with the Bank's safeguard policies. A further review of the design and implementation experience of the same sample of CBD/CDD projects was done to help identify challenges CBD/CDD operations face in applying the Bank's safeguards and assess the extent to which the interventions complied with safeguard requirements. Four broad themes emerge from the analysis: (a) although there has been clear improvement, safeguard compliance in CBD/CDD projects does not yet fully meet Bank standards; (b) while quality at entry needs improvement, safeguards compliance during implementation warrants much greater attention by the Bank and borrowers, and may indicate the need for greater allocation of supervision resources; (c) gaps in the compliance system may be leading to significant environmental and social impacts, which may not be caught by the monitoring and reporting systems typically used; and (d) the Bank appears to have particular difficulty in ensuring safeguard compliance in its largest borrowers.